(untitled) (Acta Scientiarum. Animal Sciences, 2026)
The in vitro fermentation technique has been used worldwide to study foods and feed additives in animal nutrition. There are many variations of equipment and procedures for studying digestibility and gas production. Given this, our objective was to adapt a simple, robust and low-cost fermentation bottle to simultaneously meet both requirements. The trial was performed in triplicate to evaluate the substrate incubation method (dispersed in the bottle, inside a filter bag and inside a filter bag with the addition of monensin). The adaptation of fermentation bottles has proven to be efficient for the study of in vitro fermentation because it is low cost, easy to operate, and notably allows the evaluation of fermentation products (SCFA and CH4) and digestibility to be performed simultaneously. We do not recommend the use of filter bags, as they significantly reduce IVDMD, SCFA and CH4 of the substrate by 12.6%, 18%, and approximately three times, respectively.